ASSESSING THE DISPERSION LEVELS OF TRACE ELEMENTS IN AIR FROM CONCRETE SITE BY DRY DEPOSITION - Robert, J.J.; Okidim, S.H. (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2021)
A Concrete Site and a Residential Area situated at 100 meters from the concrete Site at Terama in Port-Harcourt City were chosen for the study. Port- Harcourt City geographical coordinates are 4047' 21'' North, 60 59' 55'' East. Dry deposition on filter papers was carried out on a monthly basis for 12 months. The masses of the samples were measured by digital electronic weighing balance and subsequently subjected to Neutron Activation Analysis (NAA) to determine their elemental constituents. Neutron Activation Analysis of the concrete dust samples collected on filter papers from the concrete Site and Residential Area for the period under study revealed the presence of the following trace elements—aluminum (Al), titanium (Ti), vanadium(V), chromium (Cr), iron (Fe), manganese (Mn), nickel (Ni), rubidium (Rb), zirconium (Zr), cerium (Ce), and thorium (Th). The 8-hour time-weighted average permissible exposure limits of the trace elements for Residential Area and Concrete Site are given as follows: Al—9.20 mg/m3and 39.97 mg/m3; Ti—1.29 mg/m3 and 34.00 mg/m3; V— 0.009 mg/m3 and 0.03 mg/m3; Cr— 0.02 mg/m3 and 0.05 mg/m3; Fe—9.96 mg/m3 and 24.37mg/m3; Mn— 0.14mg/m3 and 0.26 mg/m3; Ni—0.02 mg/m3 and 0.05 mg/m3; Rb—0.05 mg/m3 and 0.08 mg/m3; Zr—0.17 mg/m3 and 0.27 mg/m3; Ce—0.04 mg/m3 and 0.63 mg/m3; and Th—0.01 mg/m3 and 0.03 mg/m3–a weak radioactive metal respectively. These values show that the trace element; Al, Ti, Fe, Mn and Ni concentrations of the samples collected during the period were higher than the 8-hour time-weighted average permissible exposure limit established by Occupational Safety and Health Administration (OSHA), recommended exposure limit by National Institute for Occupational Safety and Health (NIOSH) and threshold limit value established by American Conference of Governmental Industrial Hygienists (ACGIH). This study confirms that particles are also dispersed from concrete site to other surrounding areas, such as Residential Areas, depending on the prevailing atmospheric conditions. This means that the health and environmental impacts associated with these trace elements will be more on the Concrete Site workers than those residing at the Residential Areas located some few meters from the Concrete Sites. Exposure of workers and occupants of Residential Areas located some few meters from Concrete Site to high levels of aluminium (Al) may suffer Alzheimer’s disease. Inhalation of Titanium dust could result in breathing difficulty, coughing, and chest pain. Long time inhalation of high concentration of iron oxide fumes could result in development of a benign pneumoconiosis. Other trace elements as revealed in this study are potentially harmful to humans if inhaled in high concentration. Therefore, there is need for adequate air quality monitoring at Concrete Sites and its environs in order to avert any serious health problems associated with occupational exposure of Concrete Site workers and those living some few meters from Concrete sites.